Implementation of Community Library: a sociopolitical instrument for citizen development (Olhar de Professor, 2022)
This article aims to present an experience report that sought to reduce inequalities in access to reading through Literary Bookshelves, based on Pedagogy of Research Projects’ methodology, in a city in the interior of Bahia, especially for children and adolescents. In the development of this project, it was possible to perceive the involvement of five students of the engineering course since the first actions of the Community Library constitution. Thus, this library proved to be a sociopolitical instrument in the citizen development of the participants involved.
Keywords: Literary Bookshelf.; Social policy.; Democratization of reading.